Transventricular delivery of Sonic hedgehog is essential to cerebellar ventricular zone development - Huang, Xi (National Academy of Sciences, 2010)
Cerebellar neurons are generated from two germinal neuroepithelia: the ventricular zone (VZ) and rhombic lip. Signaling mechanisms that maintain the proliferative capacity of VZ resident progenitors remain elusive. We reveal that Sonic hedgehog (Shh) signaling is active in the cerebellar VZ and essential to radial glial cell proliferation and expansion of GABAergic interneurons. We demonstrate that the cerebellum is not the source of Shh that signals to the early VZ, and suggest a transventricular path for Shh ligand delivery. In agreement, we detected the presence of Shh protein in the circulating embryonic cerebrospinal fluid. This study identifies Shh as an essential proliferative signal for the cerebellar ventricular germinal zone, underscoring the potential contribution of VZ progenitors in the pathogenesis of cerebellar diseases associated with deregulated Shh signaling, and reveals a transventricular source of Shh in regulating neural development.